KEADILAN PEMBAGIAN HARTA WARISAN PERSPEKTIF HUKUM ISLAM DAN BURGERLIJK WETBOEK - Al-Mabruri, M. Nasikhul Umam (UIN Sunan Kalijaga Yogyakarta, 2017)
The question of the distribution of heritage property from parents to their children, or from people who have died to the parties entitled to them is a complicated problem and often cause problems for many family members. Generally, the problems arising from the practice of inheritance share are because each party feels it does not get the inheritance as it should be (unfair). This paper examines the concept of justice in the distribution of inheritance under Islamic law and Burgerlijk Wetboek (BW). This paper has provided valuable information on the understanding and concept of justice existing in Islamic law and also in BW, in which the different concept of justice has given rise to different provisions in terms of inheritance division. In the Islamic heirs law, the concept of justice is based on the principle of equitable justice, while the concept of justice contained in Burgerlijk Wetboek is built on Western philosophies and ideas, especially the justice Aristotle made about the equality of rights between individuals. Therefore, the rights of the heirs are equal to the rights of the daughter's heirs. The difference in fairness in the distribution of inheritance is due to differences in the perspectives of justice and the legal basis of the two heirs. Islam considers that the obligation to provide family support is the responsibility of men so that it is appropriate if men doubled the share of women's heritage. Meanwhile, in the Western thinking that forms the BW heir system does not determine and imposes obligations to provide a family income only to men or women, so BW's heirs provide a share of inheritance equally between men and women.